Family adoption programme for medical undergraduates in India - The way ahead: A qualitative exploration of stakeholders' perceptions - Vijay K Yalamanchili; Vijaya K Uthakalla; Sarathy P Naidana; Abhilash Kalapala; Prasanna K Venkata; Rajasekhar Yendapu (Wolters Kluwer Medknow Publications, 2023)
Introduction: Community engagement in medical education gives the students an insight into the living conditions of the public and how they influence their health. Community Medicine departments accomplish this through field practice and family health studies. The Family Adoption Programme, newly mandated for all medical undergraduate students, brings its own set of challenges and opportunities. The study aims to understand the perceptions of various stakeholders regarding this program. Material and Methods: A qualitative exploratory study was conducted. The faculty, undergraduate and postgraduate students, and field workers were purposively invited to participate. Thematic analysis was done on qualitative inputs obtained by Key Informant Interviews and Focussed Group Discussions. Results: The participants felt that FAP will provide a good insight into the patient's living conditions and also motivate the students for the kind of career they have to prepare for. The major challenges were the lack of transport and logistics in government colleges and the faculty shortage in private colleges. There was a difference of opinion regarding the right time to initiate the student into FAP. Gaining the trust and cooperation of the family and reducing the expectations were also felt important. While more field involvement by faculty was advocated, increased workload and reduced faculty requirement specifications were a matter of concern. Conclusion: While there was mixed response regarding the utility and long-term sustainability of FAP, it was hoped that with proper motivation and supervision, this program can create a significant difference in medical education and also the lives of adopted families.